Students' gestures in understanding algebraic concepts - Ida Dwijayanti; I Ketut Budayasa; Tatag Yuli Eko Siswono (Universitas Islam Negeri (UIN) Mataram, 2019)
[English]: The purpose of this qualitative exploratory study was to analyze students’ gestures in understanding algebraic expression. It involved 59 7th-grade students in Semarang city, Indonesia. Students’ gestures were identified through interviews and observations, then analyzed in three stages: data condensation, data display, and drawing and verifying conclusion. Time triangulation was utilized to assure data validity. The results showed that students employed: (1) direct gestures as a representation of coefficients and variables in the form of hand movements forming the shape of objects that they recognize in the everyday environment, (2) indirect gestures as a representation of coefficients and variables in the form of hand movements as if forming the shape of objects that they recognize in the daily environment then followed by consistent and repetitive hand movements as a representation of the coefficients, (3) direct gesture representing constants in the form of hand movements forming a specific number, and (4) writing gestures and pointing gestures to strengthen the explanation given. The present study concludes that the gestures made by the students in understanding the concepts of algebraic expression consist of representation, pointing, and writing. This study yields an important description of students' gestures and types of gestures about the algebraic concept, which provide a further understanding of the topic. Keywords: Gesture, Conceptual understanding, Algebra [Bahasa]: Penelitian kualitatif ini bertujuan untuk menganalisis gestur siswa dalam memahami bentuk aljabar. Penelitian melibatkan 59 siswa di salah satu SMP di Semarang. Data gestur siswa diidentifikasi melalui observasi dan wawancara kemudian dianalisis melalui tahapan kondensasi data, penyajian data, dan penarikan dan verifikasi simpulan. Verifikasi keabsahan data dilakukan menggunakan teknik triangulasi waktu. Hasil penelitian menunjukkan bahwa siswa menggunakan (1) gestur langsung sebagai perwujudan pemahaman konsep koefisien dan variabel dalam bentuk gerakan tangan yang membentuk objek yang dikenali dalam lingkungan sehari-hari, (2) gestur tidak langsung sebagai representasi koefisien dan variabel dalam bentuk gerakan tangan seolah-olah membentuk objek yang dikenali dalam lingkungan sehari-hari kemudian diikuti oleh gerakan tangan yang konsisten dan berulang sebagai representasi koefisien, (3) gestur langsung yang menjadi representasi konstanta melalui gerakan tangan membentuk angka tertentu, dan (4) gestur menulis dan menunjuk untuk memperkuat penjelasan yang diberikan. Penelitian ini menyimpulkan bahwa gestur yang dibentuk siswa dalam memahami konsep bentuk aljabar terdiri dari gestur representasi (gestur representasi langsung dan tidak langsung), gestur menunjuk, dan gestur menulis. Penelitian ini menghasilkan deskripsi penting tentang gestur dan jenis gestur siswa tentang konsep aljabar yang memberikan pemahaman lebih lanjut tentang topik tersebut. Kata kunci: Gestur, Pemahaman konsep, Aljabar